Co-hydrothermal carbonization of food waste-woody sawdust blend: Interaction effects on the hydrochar properties and nutrients characteristics. (November 2020) - Wang, Tengfei; Si, Buchun; Gong, Zhengjun; Zhai, Yunbo; Cao, Mingfeng; Peng, Chuan
Highlights: Effect of co-HTC on hydrochar and nutrients from FW and WS blend were investigated. High temperature and FW ratio decreased the hydrochar yield with low C retention. High temperature and FW ratio enhanced the carbonization degree of hydrochar. 10–60% of N and 82–94% of P were retained in hydrochar after co-HTC. Abstract: The influence of co-hydrothermal carbonization (co-HTC) on the hydrochar properties and nutrients distribution derived from food waste (FW) and woody sawdust (WS) blend was assessed. The carbon retention, surface functional groups and morphology features involved in hydrochar were evaluated to study the interaction effects. Results suggested that hydrochar yield consistently decreased with increase of both FW ratio and HTC temperature. C retention from 260 °C hydrochar was low (approximately 65%), but more microsphere structures was formed due to the enhanced carbonization degree of hydrochar. Hydrochar obtained at high FW blend ratio and temperature resulted in weaken oxygen-containing groups like OH and CO with enhanced CC and C(O, N). 10.43–60.45% of N and 82–94% of P were retained in hydrochar. NH4 + -N (6.63%–15.63%) and organic nitrogen (70.4%–87.7%) were identified as main N-containing species in liquid phase, while total P content (14–166 mg/L) depended more on FW ratio.